(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
The Belt and Road Initiative (BRI) is a China-led plan to boost economic growth across various global regions. China is expanding its high-speed train network, connecting Asian countries, and increasing sales of new goods and services. The BRI encourages cooperation and promotes cultural understanding, fostering communication between China and its South Asian neighbors. Its goal is to boost economic growth and foster cooperation among countries. This study is mostly about opportunities and challenges in South Asia. It is a qualitative study from the method’s point of view. This study utilized books, journals, magazines, and daily newspapers as secondary sources. This paper looks at what the BRI will mean for South Asia. Since 2013, the BRI has had an impact on both Pakistani and Indian academic policy and thinking. This study examines those effects. In light of the BRI and the many political splits in South Asia, it examines China’s place in the region. The study’s suggestions should ensure that everyone benefits from the BRI.